Indole-3-acetic acid enhances ruminal microbiota for aflatoxin B1 removal in vitro fermentation - Sun, Jiajin; Wang, Zhonghao; Yan, Xinyu; Zhao, Yuqi; Tan, Li; Miao, Xuning; Zhao, Rong; Huo, Wenjie; Chen, Lei; Li, Qinghong; Liu, Qiang; Wang, Cong; et al. (Frontiers in Veterinary Science, 2024)
Aflatoxin B1 (AFB1) has been recognized as a serious health risk for ruminant animals. From a molecular perspective, indole-3-acid (IAA) possesses the potential to enhance the removal of AFB1 by rumen microbiota. Therefore, this study aims to investigate the impact of different concentrations of IAA on the removal of AFB1 by rumen microbiota using an in vitro technique. Experiment 1: interaction between AFB1 and rumen fermentation. Experiment 2: The study used a randomized design with five IAA levels (0, 15, 150, 1,500, and 7,500 mg/kg) to examine the effect of IAA on AFB1 removal and its impact on rumen fermentation. The results showed: (1) the content of AFB1 gradually decreased, removal rate of up to 75.73% after 24 h. AFB1 exposure altered the rumen fermentation pattern, with significantly decreased in the acetic acid/propionic acid ratio (p < 0.05). It significantly reduced the relative proportions of R. amylophilus, P. ruminicola, and F. succinogenes (p < 0.05). (2) As the content of IAA increased, AFB1 exposure decreased. A total of 15 and 150 mg/kg IAA significantly mitigated the negative impact of AFB1 on key rumen bacteria (R. amylophilus, P. ruminicola and F. succinogenes), increased acetate levels and acetate/propionate ratio (p < 0.05). However, 1,500 mg/kg IAA lowered levels of propionate and isovalerate, adversely affected enzyme activities (pectinase, xylan and Carboxymethyl-cellulase) and relative proportions of microbiota (R. flavefaciens, P. ruminicola and F. succinogenes). In conclusion, IAA significantly removed AFB1, and in the range of 150 mg/kg of IAA reduced the negative effects of AFB1 on in vitro fermentation characteristics and fermentation end-products.